Rail degradation due to thermite weld discontinuities: Field experience. (October 2021) - Messaadi, Maha; Grossoni, Ilaria; Shackleton, Philip; Shevtsov, Ivan; Bezin, Yann; Dollevoet, Rolf
Highlights: We compared the failure of railway thermite welds through real field-testing. We simulated the dynamic impact force induced by the weld geometry. We reported the progression of the surface hardness of welds in track condition. We discussed the noticed failures; wear and cracks. Abstract: This paper details the field-testing approach and results of thermite welds used in railway applications. Rail steels made from R260 grades are welded by two different processes: the standard process according to the European standards, and a recent technology. Welds are introduced in the same testing location to ensure comparable loading conditions in the aim of studying their degradation behaviours. The total testing-period is 6 months. During the in-service period, the surface hardness of the running band, in the welded area, is recurrently measured. For an accurate assessment of field results, a vehicle/track interaction (VTI) model evaluated the expected dynamic loads induced by the initial vertical irregularities. The simulations show that the highest dynamic load at the wheel/rail contact happens at the location of the maximum absolute gradient, in accordance with previous research. Particularly, dipped welds show relatively high dynamic forces inducing a high loss of the transversal profile. In respect of the field results, the comparison of initial and final surface hardness indicates a significant increase for 'ALFONS' welds over the welded areas. Additionally, all welds depicted a cyclic increase and decrease of the running band hardness. This result is discussed according to the ratcheting susceptibility of welds and eventual wear progression. For a testing-period of 10 weeks, the gauge corner of one 'ALFONS' weld developed a crack. The assessment of the longitudinal profiles revealed changes of the vertical irregularities that may modify the dynamic loads, and further the rolling contact fatigue mechanisms and degradation rates.